1989
DOI: 10.1016/0266-7681_89_90127-7
|View full text |Cite
|
Sign up to set email alerts
|

Homodigital Neurovascular Island Flaps for Digital Pulp Loss

Abstract: Terminal amputations with loss of the distal pulp are common injuries. This report analyses 64 consecutive cases of advanced or exchanged homodigital neurovascular island flaps operated on by one surgeon between 1981–1986. The surgical technique, indications, contra-indications and five year results are evaluated. Overall, these flaps provide reliable vascularity as well as normal sensibility at the distal end of the finger where high quality perception is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…As in the larger series, such as those of Foucher et al (1989) and Smith and Elliot (2000) and the systematic review performed by Castillo et al (2022), we found a low incidence of complications. In particular there were no cases of complete flap necrosis, despite most surgeons in our study not being experienced hand surgeons.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As in the larger series, such as those of Foucher et al (1989) and Smith and Elliot (2000) and the systematic review performed by Castillo et al (2022), we found a low incidence of complications. In particular there were no cases of complete flap necrosis, despite most surgeons in our study not being experienced hand surgeons.…”
Section: Discussionsupporting
confidence: 76%
“…1 Service de Chirurgie de la Main et du Membre Sup erieur, Ho ˆpital Edouard Herriot, Lyon, France 2 Venkataswami and Subramanian (1980), and Mouchet and Gilbert (1982), described the use of a monopedicled anterior neurovascular island flap; however, the pedicle was short. Foucher et al (1989) and Schuind et al (1985) designed flaps that were similar to those of Segmu ¨ller and Biddulph, with a single and longer neurovascular pedicle, but without a proximal V-to-Y tail; this flap requires a skin graft to the donor defect. In a large series, Smith and Elliot (2000) avoided the use of a skin graft in the Foucher flap by adding a Segmu ¨ller V-incision, which was either closed as a Y or, in most cases, left open to heal secondarily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement island is itself not a recent proposal and Segmuller [6] has isolated a Kutler flap as an island in order to increase mobility. This idea was subsequently taken up by numerous authors [15,19,[22][23][24]. It was in the index finger that we were able to obtain the most significant advancement (maximum 22 mm by "medialization" of the pedicle).…”
Section: Homo-digital Island Flapsmentioning
confidence: 92%
“…The relative contraindication is the presence of arteritis or small vessel disease. This flap is not recommended in the presence of gross contamination or avulsion injury 19…”
Section: Indications and Contraindicationsmentioning
confidence: 99%